Feeding, crop residue and manure management for integrated soil fertility management—A case study from Kenya - Castellanos-Navarrete, A.; Tittonell, Pablo A.; Rufino, Mariana C.; Giller, Kenneth E. (Elsevier, 2015)
Western Kenya is one of Africa’s most densely populated rural areas, characterised by intensive smallholder crop–livestock systems on degraded lands managed with small inputs of mineral fertiliser and animal manure. Competing uses for crop residues and other organic resources often results in poor nutrient cycling efficiencies at farm scale. Modifying livestock feeding, retaining more crop residues in the field, and improving manure management can help conserving considerable amount of nutrients on-farm. To examine to what extent such strategies would be feasible, we analysed whole-farm nutrient cycling efficiencies (NCE) of a range of farms differing in resource-endowment and production orientation, identifying the most efficient farmer strategies considering labour and financial constraints. Nutrient concentration in excreted cattle manure was relatively small (i.e., N < 1.7%; P < 0.6%). Current manure management practices led to low NCE’s (average 27%) due to nutrient losses from excretion through storage and application. Farmers have few incentives to improve manure management given the small amounts of excreta and nutrients to be recycled. Yet, manure, both composted and fresh, represented the greatest N (16 kg ha−1 season−1) and C returns to the soil (312 kg C ha−1 season−1). Retention of crop residues was the cheapest source of nutrient inputs for the next crop, especially when compared with manure, but farmers prioritised its use for cattle feeding. Our findings highlight the critical lack of nutrients and organic residues on smallholder farms in the densely-populated highlands of East Africa, as well as low NCE when it comes to manure. In these conditions, efficient nutrient cycling for manure and improved cattle feeding are essential to increase use efficiencies of any possible external nutrient added in these farms.